Correction: Mekonnen et al. Modeling, Analysis and Optimization of Grid-Integrated and Islanded Solar PV Systems for the Ethiopian Residential Sector: Considering an Emerging Utility Tariff Plan for 2021 and Beyond. Energies 2021, 14, 3360 - Tefera Mekonnen; Ramchandra Bhandari; Venkata Ramayya (Energies, 2022)
The authors wish to make the following corrections to their paper [...]